Infrastruktur Kota Ramah Pesepeda: Ruang Parkir Koridor Puputan Renon–Hangtuah Sanur, Denpasar - Paramitha, I Gusti Ayu Intan; Suartika, Gusti Ayu Made; Adhika, I Made (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 11 No 2 (2024): October 2024, 2024)
This article is about creating a cyclist-friendly city, taking a case study of Denpasar, which promotes sustainable infrastructures, particularly those dedicated to bicycles. In line with the Indonesian Ministry of Transportation’s Regulation No. 59 of 2020, which outlines the safety and accessibility of public parking for bicycles, it concentrates its discussions on the provision of such infrastructure for the Puputan Renon-Hangtuah Sanur Corridor of Kota Denpasar. This research employs a descriptive qualitative method, utilizing in-depth interviews as a data collection method. Its respondents include those coming from cycling communities and government agencies. Study findings will support the local government’s initiative to develop urban infrastructures that encourage public interest in cycling. This study has produced a map demonstrating potential bicycle parking spots along the Puputan Renon-Hangtuah Corridor in Denpasar. Locations of these spots have been based on respondents’ recommendations and include public facilities, shopping centers, and academic institutions. This map would recommend developing Denpasar as a cyclist-friendly city by providing safe and accessible bicycle parking spaces. Keywords: infrastructure; bike lanes; parking; safety   Abstrak Artikel ini mendiskusikan tentang pembangunan kota ramah pesepeda dengan mengambil studi kasus di Denpasar, kota yang mempromosikan pembangunan infratruktur berkelanjutan, khususnya yang didedikasikan untuk sepeda. Beriringan dengan Permenhub   Nomor 59 Tahun 2020 yang menjelaskan keamanan dan aksesibilitas ruang parkir publik untuk sepeda, artikel ini  mengkonsentrasikan pembahasannya pada pengadaan infrastruktur untuk Koridor Puputan Renon-Hangtuah Sanur di Kota Denpasar. Penelitian ini menerapkan metode kualitatif deskriptif dengan memanfaatkan interview mendalam sebagai metoda pencarian data. Para responden berasal dari komunitas pesepeda dan instansi pemerintah. Temuan studi akan menjadi rekomendasi kepada pemerintah lokal untuk membangun infrastruktur kota yang medorong minat masyarakat dalam bersepeda. Studi ini memproduksi sebuah peta yang menunjukkan titik-titik parkir yang potensial di sepanjang Koridor Puputan Renon-Hangtuah Sanur. Lokasi titik-titik ini didasari atas rekomendasi yang diberikan oleh para responden yang melingkupi fasilitas publik, pusat perbelanjaan dan kawasan akademik. Hasil penelitian ini dapat dijadikan rekomendasi untuk pembangunan Denpasar sebagai kota ramah pesepeda dengan membangun ruang-ruang parkir bagi sepeda yang aman dan bisa diakses. Kata kunci: infrastruktur; jalur sepeda; parkir; keamanan